University Teacher Training in Japan - Kaori Kato (Universitat Politècnica de València, 2013)
University teacher training in Japan has been promoted as a part of 'Faculty Development (FD)'. Teacher training became a 'substantial duty' to faculties for of undergraduate schools by a ministerial ordinance in 2008 (graduate schools in 2007). However, contents of the Faculty Development are left to each organisation's discretion, and the ordinance does not have the legal right to mandate the participation of all academic staff in teacher training. In the 2000s, Japanese universities were under the external pressures such as quality assurance inspections, acquisition of external funds, and the exposure of data about their students. These circumstances have promoted the movements of the Faculty Development as KAIZEN (collective improvement by means of the plan-do-check-action cycle) activities of education at institutions. However, a few institutions offer a systematised programme of teaching and learning for academic staff. The teacher training for enhancement of teaching skills is still not a priority in Japan.